Consolidation of Memory After its Reactivation: Involvement of ß Noradrenergic Receptors in the Late Phase - Pascal Roullet; Susan Sara (Neural Plasticity)
Evidence is growing that the cAMP pathway through the cAMP responsive element binding protein (CREB) transcription factor plays an important role in long-term memory formation (LTM). To study the role of ß-noradrenergic receptors, positively linked to the cAMP secondmessenger system, in the dynamics of LTM processes, we used a memory-reactivation paradigm because recent studies in our laboratory confirmed that reactivated memory is labile and undergoes an extended reconsolidation process. In an eight-arm maze, rats were trained to choose the same three baited arms; 24 hr later, memory was reactivated and then the rats were injected intracerebroventricularly at 5 min, 30 min, 60 min, or 5 hr later with the ß-antagonist timolol or with saline. The results showed that injection of timolol induced amnesia only at the 60 min post-reactivation interval, whereas all control groups and groups that were timolol-injected at other post-reactivation intervals displayed optimal retention. The delayed amnesic action of timoloi suggests that ß noradrenergic receptors and the cAMP cascade are implicated in the late phase of reprocessing of a remembered event.